2013
DOI: 10.1007/s00056-013-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

Lateral cephalometric standards of Germans with normal occlusion from 6 to 17 years of age

Abstract: The aim of this study was to analyze sagittal and vertical dentofacial dimensions in subjects with normal occlusions during the juvenile and adolescents age periods to establish age- and gender-specific lateral cephalometric standard values for Germans during their active growth period. The study group consisted of a sample of 32 untreated subjects with normal occlusions. Lateral cephalograms were analyzed at 11 consecutive stages, from 6-13 and from 15-17 years of age. A customized cephalometric analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Recent studies have shown that cephalometric linear measurements increased with age, while angular measurements appeared more constant [13]. In the presence of a normal occlusion, the craniofacial complex grows continuously in a downward and anterior direction along the Downs facial axis, and this process is not gender-specific [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cephalometric linear measurements increased with age, while angular measurements appeared more constant [13]. In the presence of a normal occlusion, the craniofacial complex grows continuously in a downward and anterior direction along the Downs facial axis, and this process is not gender-specific [14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Trotman and Ross [25] found the same results in a group of patients with complete bilateral cleft lip and palate between 6 and 12 years and as grown-ups. They also observed a decrease of SNA as consequence of surgical procedures, since SNA undergoes a physiologic increase during growth in non-cleft patients [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic clinicians and researches benefit from the existence of gender-and age-specific standard values for specific populations for several reasons [13]. Standard values are of great help in diagnostics and treatment planning, especially in growing children in whom alveolar and dental changes occur continuously [10,40].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, assessment of treatment outcome is more accurate by comparing natural growth changes in untreated subjects with normal occlusion rather than with controls displaying different types of malocclusion [34]. Therefore, several studies were carried out in the past to investigate longitudinal dental changes in untreated children and adolescents [4,5,7,12,13,15,20,24,27,32,[34][35][36][38][39][40]. However, only a few of them have described dental and soft tissue changes from the deciduous to the permanent dentition [5,7,8,32,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation